Food habits of three species of mudskippers in the Musi River Estuary, South Sumatra, Indonesia - Moh Rasyid Ridho; Enggar Patriono; Mar'atus Solikha (Society for Indonesian Biodiversity, 2019)
Abstract. Ridho MR, Patriono E, Sholikah M. 2019. Food habits of three species of mudskippers in the Musi River Estuary, South Sumatra, Indonesia. Biodiversitas 20: 2368-2374. This study provided understanding of morphometric variation and diet composition of three species of mudskippers, i.e. Boleophthalmus boddarti, Periophthalmodon schlosseri, and Periophthalmus chrysospilos. The data obtained can be used for fish cultivation in the future. The relation of weight and length of species B. boddarti, P. schlosseri and P. chrysospilos had a correlation of 72.2%, 98.2%, and 94.5%, respectively with the value of b = 1.474, 3.189, and 2.271, respectively. This suggests that the growth patterns of B. boddarti and P. chrysospilos are allometrically negative, while P. schlosseri is allometrically positive. B. boddarti is classified as a herbivore, the main food of phytoplankton from Bacillariophyceae class with percentage 100%; 80% of Chlorophyceae; 95.6% of Cyanophyceae; 13.33% of Desmidiaceae; 13.33% of Euglenophyceae and 37.78% of Xanthophyceae. P. schlosseri is classified as carnivores, the main food is Uca sp. with IRI of 17.131.45% and complimentary food of Lycosa sp. with IRI of 80.79%. P. chrysospilos is also classified as carnivores with the main food is fish eggs with IRI of 8057.07% and complementary foods of Uca sp. with IRI of 1935.3%.